Miscellany/Mélanges - Mason, H (Voltaire Foundation, 2017)
James L. Schorr, Les Petits-Maîtres and La Critique by Justus van Effen Roland G. Bonnel, Le despotisme dans les Lettres persanes Sheila Mason, Montesquieu on English constitutionalism revisited: a government of potentiality and paradoxes William H. Trapnell, Destiny in Voltaire’s Zadig and The Arabian nights Moishe Black, The place of the human body in Candide Marie Wellington, Crossovers from theatre to narrative in a Voltairian conte E. P. Abanime, Les noirs dans l’œuvre romanesque de Voltaire Jean-Claude David, De Voltaire à Marmontel: quelques autographes du dix-huitième siècle réunis par Jacques Charavay (1809–1867) Giovanna Gronda, De la satire à la parodie: de Voltaire à Monti — la traduction italienne de la Pucelle d’Orléans Walter E. Rex, Sexual metamorphoses on the stage in mid-eighteenth-century Paris: the theatrical background of Rousseau’s Narcisse Guillemette Johnston, The divided self in La Nouvelle Héloïse Anna Ridehalgh, Rousseau as God? The Ermenonville pilgrimages in the Revolution Diane Fourny, L’Emile et la question du livre Guy Wagener, What in the devil’s name is Jacques le fataliste? Vincent McB. Tobin, Gluck’s Iphigénie en Tauride: an eighteenth-century Euripidean drama Alexander Sokalski, Grammars and grottos: language learning and language teaching in pre-revolutionary Paris, 1780–1789 Santo L. Arico, Elitism versus popularism in the educational treatises of La Chalotais, Morveau and Rolland D. D. Raphael, D. R. Raynor, I. S. Ross, “This very awkward affair”: an entanglement of Scottish professors with English lords Leonore Loft, J.-P. Brissot and the problem of Jewish emancipation